EKSPLORASI IMPLEMENTASI BIMBINGAN DAN KONSELING PENDIDIKAN DASAR DI MALAYSIA - Tri Sutrisno; Adawiyah, Rabiatul (UHN IGB Sugriwa Denpasar, 2025)
This study aims to explore the implementation of guidance and counseling services in Malaysian elementary schools and to identify adaptation ideas that may be applied in other countries. The research employed a qualitative approach with a case study design conducted at Sekolah Kebangsaan Telok Panglima Garang, Selangor, Malaysia. Data were collected through interviews with classroom teachers and documentation of counseling programs, and analyzed using the interactive model of Miles, Huberman, and Saldaña. Data validity was ensured through triangulation of sources, techniques, and contextual description. The findings indicate that guidance and counseling in Malaysian elementary schools are carried out professionally by Full-Time Guidance and Counseling Teachers (Guru Bimbingan dan Kaunseling Sepenuh Masa / GBKSM) using holistic, preventive, and collaborative approaches. Innovative programs such as mentor-mentee, peer counseling, and the utilization of digital counseling have proven effective in supporting students’ academic, emotional, and social development. The success of the implementation is further strengthened by curriculum integration, the establishment of counseling units, national guidelines, as well as active involvement of parents and the community. The study recommends several adoption strategies, including the placement of specialized counseling teachers in elementary schools, integration of counseling services into the curriculum, teacher capacity building, the use of technology, and modifications tailored to local cultural contexts. These findings emphasize that guidance and counseling services play a crucial role in fostering inclusive, high-quality, and sustainable primary education.